(3GdLGeY GdUMjMs - (3eSde Hf GdMLGL Hf eSde GdbTjQj GdfjSGHhQqi, CHh GdMSjf, CHh GdMSjf,J (B261 (3g` s ((3YHOGddg Hf eMeO Hf eWgQ GdfMhi s)
(3ChdgG (B:s
(3cJGH aVGFd GdbQBf HGH cja fRhd hChd eG fRd s
(3BNQgG (B:s
(3Yf CHj gQjQI bGd bGd GdfHi Udi Gddg Ydjg hSde(B: (3cdeJGf MHjHJGf Edi GdQMef NajaJGf Ydi GddSGf KbjdJGf ai GdejRGf SHMGf Gddg hHMeOg SHMGf Gddg GdYXje Je BNQ GdSaQ GdKGdK ef UMjM GdHNGQi s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B221 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B232s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B541s
Keywords: (3GdMOjK h GdeUWdMs